2012
DOI: 10.1007/s13595-012-0241-0
|View full text |Cite
|
Sign up to set email alerts
|

Drought sensitivity of Norway spruce is higher than that of silver fir along an altitudinal gradient in southwestern Germany

Abstract: For Central Europe, climate projections foresee an increase in temperature combined with decreasing summer precipitation, resulting in drier conditions during the growing season. This might negatively affect forest growth, especially at sites that are already water-limited, i.e., at low elevation. At higher altitudes trees might profit from increasing temperatures. We analyzed variations in radial growth of silver fir (Abies alba Mill.) and Norway spruce (Picea abies (L.) Karst.) along an altitudinal gradient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(48 citation statements)
references
References 48 publications
6
41
0
1
Order By: Relevance
“…Moreover, both hydraulic and carbon constraints (Herms & Mattson, ; McDowell et al, ) can lead to general metabolic limitations as indicated by impaired carbon transport from sources to sinks (Ruehr et al, ) or reduced allocation to defense compounds (McDowell et al, ) and the consequences thereof might strongly determine the recovery trajectories. Our findings are in agreement with recent dendroecological studies showing a higher vulnerability of spruce and larch to drought than fir (Lévesque et al, ; van der Maaten‐Theunissen, Kahle, & Maaten, ; Vitali, Buntgen, & Bauhus, ), which is also in line with studies showing a high sensitivity of spruce to elevated VPD (Sanginés de Cárcer et al, ) and the inability of its root system to access deep water layers during summer drought (Brinkmann, Eugster, Buchmann, & Kahmen, ). Our study also confirms that sessile and pedunculate oaks are able to cope with severe hot drought, as previously suggested in a study focusing on its water status and photosynthesis during the extremely hot drought in 2003 (Leuzinger, Zotz, Asshoff, & Körner, ).…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, both hydraulic and carbon constraints (Herms & Mattson, ; McDowell et al, ) can lead to general metabolic limitations as indicated by impaired carbon transport from sources to sinks (Ruehr et al, ) or reduced allocation to defense compounds (McDowell et al, ) and the consequences thereof might strongly determine the recovery trajectories. Our findings are in agreement with recent dendroecological studies showing a higher vulnerability of spruce and larch to drought than fir (Lévesque et al, ; van der Maaten‐Theunissen, Kahle, & Maaten, ; Vitali, Buntgen, & Bauhus, ), which is also in line with studies showing a high sensitivity of spruce to elevated VPD (Sanginés de Cárcer et al, ) and the inability of its root system to access deep water layers during summer drought (Brinkmann, Eugster, Buchmann, & Kahmen, ). Our study also confirms that sessile and pedunculate oaks are able to cope with severe hot drought, as previously suggested in a study focusing on its water status and photosynthesis during the extremely hot drought in 2003 (Leuzinger, Zotz, Asshoff, & Körner, ).…”
Section: Discussionsupporting
confidence: 93%
“…Our simulation indicates that A. alba can grow under lower moisture conditions than Picea abies in the study area, which is in agreement with ecological studies (e.g. Zingg & Bürgi, ; Ellenberg & Leuschner, ; van der Maaten‐Theunissen et al ., ). Indeed, the expansion of silver fir at ca.…”
Section: Discussionmentioning
confidence: 97%
“…Scots pine and silver fir were insensitive to temperature. Both species are known to be less temperature and drought sensitive than spruce at low elevation sites (van der Maaten‐Theunissen, Kahle & van der Maaten ; Lévesque et al . ; Zang et al .…”
Section: Discussionmentioning
confidence: 99%